The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.jchromb.2012.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Determination of celiprolol in human plasma using high performance liquid chromatography with fluorescence detection for clinical application

Abstract: A new method of analysis has been developed and validated for the determination of plasma celiprolol concentration. Plasma samples (1 ml) were pre-purified by solid-phase extraction with Bond Elut C18. The separation was achieved with XBridge C18 column (150 mm × 3.0mm i.d., 3.5 μm) at 35 °C using a mixture of acetonitrile and 10mM ammonium acetate buffer (pH 10.5) (34:66, v/v) under isocratic conditions at a flow rate of 0.4 ml/min. The peak was detected using a fluorescence detector at excitation 250 nm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…A double-peak phenomenon was observed for celiprolol only, which was consistent with our and other previous findings. 5,22,23 Regional differences have been reported in the intestinal mRNA expression of OATP2B1; Meier et al 24 measured the increased expression of OATP2B1 longitudinally along the intestine (ileum > colon descendens ¼ colon transversum > colon ascendens ¼ duodenum). Although the reason for this currently remains unclear, the site dependence of intestinal absorption is the most likely cause.…”
Section: Resultsmentioning
confidence: 99%
“…A double-peak phenomenon was observed for celiprolol only, which was consistent with our and other previous findings. 5,22,23 Regional differences have been reported in the intestinal mRNA expression of OATP2B1; Meier et al 24 measured the increased expression of OATP2B1 longitudinally along the intestine (ileum > colon descendens ¼ colon transversum > colon ascendens ¼ duodenum). Although the reason for this currently remains unclear, the site dependence of intestinal absorption is the most likely cause.…”
Section: Resultsmentioning
confidence: 99%
“…We had already a developed HPLC method with alkaline conditions for the analysis of basic compound [15,16] in human plasma, by using XBridge™ C18 (5µm, 150mm x 4.6mm i.d. ; Waters) with fluorescence detection.…”
Section: Resultsmentioning
confidence: 99%
“…In clinical pharmacokinetic studies that require a large number of sample analyses, the SPE method reported here may be suitable because of its labor-and time-saving advantages. We have already successfully used SPE method with Bond Elut C18 ® column for analysis fexofenadine [15] and celiprolol [16]. In the present study, the Bond Elut C18 ® column was applied for the determination of domperidone in human plasma.…”
Section: Sample Preparationmentioning
confidence: 95%
“…Itohda and colleagues [1] conducted an investigation employing Solid-Phase Extraction (SPE) to determine the concentration of celiprolol in human plasma. The quantification of this analyte was accomplished through the utilization of High-Performance Liquid Chromatography (HPLC) in conjunction with a fluorescence detector (FLD).…”
Section: Liquid Chromatography and Related Methodsmentioning
confidence: 99%